Protecting Blueberries from Freezes in Florida - J. G. Williamson; Doug Phillips (EDIS, 2023)
Blueberries bloom in late winter or early spring in Florida, making the flowers and young fruit highly susceptible to freeze and frost injury. Killing freezes can occur as late as mid to late March throughout much of Florida, long after the initiation of bloom, especially for early-ripening southern highbush blueberry cultivars. This publication describes conditions that often occur in commercial blueberry fields during and after bloom when the potential for freeze damage exists. Practices that growers can use to minimize freeze damage are also discussed.